Perfil funcional de pacientes com câncer de mama submetidas ao tratamento de fisioterapia no Grupo de Educação e Estudos Oncológicos - Lima, Ângela Maria Vidal (2021)
This research presents the functional profile of patients with breast cancer submitted to physical therapy treatment at the Education and Oncological Studies Group (GEEON), extension of the Federal University of Ceará (UFC). The program of the Physiotherapy Service was based on the routine of Physiotherapy in Oncology Mastology at the National Cancer Institute (INCA). The study aimed to verify the functional profile related to physiotherapeutic treatment in the preoperative, immediate postoperative phases, follow-up from 30 to 180 days, discharge and reassessment upon the appearance of complications. It was a descriptive-exploratory, retrospective, longitudinal study, with quantitative analysis. The period covered the years 2018 to 2020. There were 501 women diagnosed with breast cancer. The sample consisted of 88 women who met the inclusion criteria. Data were collected from patients' medical records. Information on 22 variables was extracted, taken from the Evaluation Form, totaling 1,936 data. The data were tabulated in the Microsoft Excel program, and extracted to GraphPad Prism, version 9.0. There was inferential statistical analysis, calculation of measures of central tendency and specific tests for the findings with P<0.05. The results were presented in tables and graphs. The research respected the ethical aspects that deal with research involving human beings, with Approval Opinion No. 4,564,594 from CEP/HUWC. The normality test using the association of the D'Agostino & Pearson Test, obtained heterogeneous results in the 22 variables analyzed and in those compared to each other, with a P> 0.001, showing the statistical significance between the analyzes and in the Bonferroni post-test (homoscedasticity) for P> 0.005 and heteroscedasticity for P<0.005). It was concluded that the routine of the Physiotherapy Service implemented at GEEON provided an improvement in the functional profile of the patients attended, a return to instrumental activities of daily living and activities of daily living, with a consequent improvement in quality of life and self-esteem. The results of the physical therapy intervention were statistically significant.